Acquired Form of Angioedema of the Head and Neck Related to a Deficiency in C1-Inhibitor: A Case Report with a Review of the Literature - Bassel Hallak; Propser Konu; Florian Lang; Christian Simon; Philippe Monnier (Case Reports in Otolaryngology)
Angioedema related to a deficiency in the C1-inhibitor protein is characterized by its lack of response to therapies including antihistamine, steroids, and epinephrine. In the case of laryngeal edema, mortality rate is approximately 30 percent. The first case of the acquired form of angioedema related to a deficiency in C1-inhibitor was published in 1972. In our paper, we present a case of an acquired form of angioedema of the oropharyngeal region secondary to the simultaneous occurrence of two causative factors: neutralization of C1-inhibitor by an autoantibody and the use of an angiotensin convertin enzyme inhibitor.